PEMBANGUNAN JALAN MAKAM RT. 01 RW.05 DESA KEDUNGLEPER KECAMATAN BANGSRI KABUPATEN JEPARA - Yayan Adi Saputro; Muhammad Khoirul Mahfidh (Jurnal Pengabdian Masyarakat Multidisiplin, 2020)
Community service activities by lecturers and students of the Civil Engineering study program, Faculty of Science and Technology, Islamic University of NahdlatulUlamaJepara at RT. 01 RW. 05 Kedungleper Village, Bangsri District is the construction of a concrete road (rigid pavement) to the tomb along 28 m, 3 m wide, and 0.12 m thick. Activities carried out include planning, implementation, monitoring and evaluation. The planning carried out by this community service team together with the village and community development team made drawings and RABs to be submitted to the village development planning deliberations. The implementation is carried out after approval of the proposal given by involving community assistance (community self-help) in 2 parts according to the day. On the first day there were 16 people doing self-help and on the second day there were 16 people. During the implementation process, the quality of work produced is carried out so that the results obtained are of good quality according to the plan.